Nap with Baby Yeti: sleeping meditation for kids - Wurfel, Marlene (My University, 2018)
This episode is a sleeping meditation. Get comfortable -- may cause drowsiness, relaxation, well-restedness and peace and quiet. Dedicated to naptime all around the world -- yay for naps!
Keywords: storytelling; children's stories